Soluble CD30 and ELISA-detected human leukocyte antigen antibodies for the prediction of acute rejection in pediatric renal transplant recipients - Billing, Heiko; Sander, Anja; Süsal, Caner; Ovens, Jörg; Feneberg, Reinhard; Höcker, Britta; Opelz, Gerhard; Tönshoff, Burkhard (Transplant international, 2013)
Biomarker-based post-transplant immune monitoring for the prediction of impending graft rejection requires validation in specific patient populations. Serum of 28 pediatric renal transplant recipients within the framework of a well-controlled prospective randomized trial was analyzed pre- and post-transplant for soluble CD30 (sCD30), a biomarker reflecting mainly T-cell reactivity, and anti-human leukocyte antigen (anti-HLA) antibody reactivity, a biomarker for B-cell activation. A sCD30 concentration ≥40.3 U/ml on day 14 was able to discriminate between patients with or without biopsy-proven acute rejection (BPAR) with a sensitivity of 100% and a specificity of 76%. Six of seven patients (86%) with BPAR showed a sCD30 above this cut-off, whereas only 3/21 patients (14%) without BPAR had a sCD30 above this cut-off (P = 0.004). For pre- and post-transplant anti-HLA class II reactivities by enzyme-linked immunosorbent assay, a cut-off value of 140 optical density was able to discriminate rejecters from nonrejecters with a sensitivity of 86% or 71% and a specificity of 81% or 90%, respectively. Withdrawal of steroids was associated with a approximately twofold higher serum sCD30 compared to controls, but did not affect anti-HLA reactivities. An increased post-transplant sCD30 serum concentration and positive pre- and post-transplant anti-HLA class II reactivities are informative biomarkers for impending BPAR in pediatric renal transplant recipients. (TWIST, Clinical Trial No: FG-506-02-43)